Waterbirds (other than Laridae) nesting in the middle section of Laguna Cuyutlán, Colima, México - Mellink, Eric (2008)
Laguna de Cuyutlán, in the state of Colima, Mexico, is the only large coastal wetland in a span of roughly 1150 km. Despite this, the study of its birds has been largely neglected. Between 2003 and 2006 we assessed the waterbirds nesting in the middle portion of Laguna Cuyutlán, a large tropical coastal lagoon, through field visits. We documented the nesting of 15 species of non-Laridae waterbirds: Neotropic Cormorant (Phalacrocorax brasilianus), Tricolored Egret (Egretta tricolor), Snowy Egret (Egretta thula), Little Blue Heron (Egretta caerulea), Great Egret (Ardea alba), Cattle Egret (Bubulcus ibis), Black-crowned Nightheron (Nycticorax nycticorax), Yellow-crowned Night-heron (Nyctanassa violacea), Green Heron (Butorides virescens), Roseate Spoonbill (Platalea ajaja), White Ibis (Eudocimus albus), Black-bellied Whistling-duck (Dendrocygna autumnalis), Clapper Rail (Rallus longirostris), Snowy Plover (Charadrius alexandrinus), and Black-necked Stilt (Himantopus mexicanus). These add to six species of Laridae known to nest in that area: Laughing Gulls (Larus atricilla), Royal Terns (Thalasseus maximus), Gull-billed Terns (Gelochelidon nilotica), Forster's Terns (S. forsteri), Least Terns (Sternula antillarum), and Black Skimmer (Rynchops niger), and to at least 57 species using it during the non-breeding season. With such bird assemblages, Laguna Cuyutlán is an important site for waterbirds, which should be given conservation status.